2003
DOI: 10.1007/s00441-003-0796-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of MAP1A, MAP1B, and MAP2A&B during layer formation in the optic tectum of developing chick embryos

Abstract: The expression patterns of three microtubule-associated proteins (MAP1A, MAP1B, and MAP2A&B) were investigated in the developing optic tectum. Expression of MAP1B and middle-molecular-weight peptide of neurofilament (NF-M) was first observed in the same mesencephalic cells on day 3 of incubation, indicating that neuroblasts had been produced. At day 5, MAP1A and MAP2A&B expression appeared in the cellular layer containing the first neuroblasts that differentiate into large multipolar cells. The NF-M+ neurites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We found that microtubule-associated protein 2 (MAP2), a neuronal marker, was also expressed in layers IV/V ( Fig. 1D-F; Yasuda and Fujita, 2003). Expression of Sema3A, a ligand for NRP1, was localized in layer VI (Fig.…”
Section: Sema3a and Nrp1 Are Expressed In Distinct Tectal Layersmentioning
confidence: 86%
“…We found that microtubule-associated protein 2 (MAP2), a neuronal marker, was also expressed in layers IV/V ( Fig. 1D-F; Yasuda and Fujita, 2003). Expression of Sema3A, a ligand for NRP1, was localized in layer VI (Fig.…”
Section: Sema3a and Nrp1 Are Expressed In Distinct Tectal Layersmentioning
confidence: 86%
“…Live imaging in these neuro-2a cells shows that MAP2c triggers neurite formation through rapid accumulation and bundling of stable MAP2c bound microtubules, and in hippocampal neurons loss of either the MAP2c microtubule binding domain or the protein kinase A binding domain of MAP2c impairs neurite formation (Dehmelt et al, 2006). The expression of the higher molecular weight MAP2a and MAP2b isoforms generally occurs after neurite growth and during neuron maturation, however their expression has been observed in developing neuroblasts in the optic tectum preceding differentiation into multipolar cells, but the roles of MAP1a and MAP2b with respect to neurite initiation in this case are unknown (Matus et al, 1990; Schoenfeld and Obar, 1994; Yasuda and Fujita, 2003). …”
Section: Regulation Of Microtubules By Mapsmentioning
confidence: 99%